A GoldenBraid cloning system for synthetic biology in social amoebae. Issue 8 (30th March 2020) - Kundert, Peter; Sarrion-Perdigones, Alejandro; Gonzalez, Yezabel; Katoh-Kurasawa, Mariko; Hirose, Shigenori; Lehmann, Peter; Venken, Koen J T; Shaulsky, Gad
Abstract: GoldenBraid is a rapid, modular, and robust cloning system used to assemble and combine genetic elements. Dictyostelium amoebae represent an intriguing synthetic biological chassis with tractable applications in development, chemotaxis, bacteria–host interactions, and allorecognition. We present GoldenBraid as a synthetic biological framework for Dictyostelium, including a library of 250 DNA parts and assemblies and a proof-of-concept strain that illustrates cAMP-chemotaxis with four fluorescent reporters coded by one plasmid.